PERAN ARTIFICIAL INTELLIGENCE (AI) DALAM ETIKA AKADEMIK PADA PENYUSUNAN MAKALAH: STUDI KASUS MAHASISWA BARU PENDIDIKAN AGAMA ISLAM - Tyana, Irma; Odik Afifin, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to investigate how new students in the Islamic Religious Education (PAI) Study Program at Al-Qolam University Malang, negotiate and use artificial intelligence (AI). The study examines the relationship between the traditional values ​​of a pesantren-based campus and the demands of academic digitization using a qualitative approach and data triangulation techniques, including document analysis of student papers, in-depth interviews with three selected informants, and a questionnaire with thirty respondents. The results indicate that AI has emerged as an important practical resource, helping students overcome challenges related to accessing literary works and managing their limited time, particularly beneficial for students juggling academic and work responsibilities. We categorize AI users into three distinct groups: the idealistic-critical type, who prioritize unique thinking with a deep understanding of concepts; the pragmatic-adaptive type, who focus on maximizing productivity; and the pragmatic-effective type, who prioritize the visual appeal and overall quality of their work. Combining multiple data sources reveals a gap between shared understandings of ethical behavior and actual behavior, as students often accept computer-generated quotations without verifying their accuracy. This study recommends that universities implement comprehensive policies and enhance digital skills training based on Islamic principles, with the aim of protecting students' intellectual integrity during this period of rapid technological change.